2012
DOI: 10.1590/s0101-32622012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Gênero, corpo e sexualidade: negociações nas brincadeiras do pátio escolar

Abstract: RESUMO:A partir das vertentes dos estudos culturais e de gênero, pretendo problematizar como são atribuídos/constituídos/atravessados significados de gênero nas práticas corporais vivenciadas pelas meninas e pelos meninos. Indago como o corpo, as práticas corporais e as brincadeiras acontecem no pátio escolar. Realizei um estudo etnográfico durante um ano numa escola pública de Porto Alegre (RS), focalizando turmas da primeira a quarta séries, mapeando brincadeiras e negociações de gênero e de sexualidade que,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
4
0
8
Order By: Relevance
“…In Table 6 you can see the frequency of articles by type of effect. It can be observed that in the researched literature, the results are statis tically significant in 60.87% of production, totaling 14 articles (SEFFNER, 2011;WENETZ, 2012;RABELO, 2013;ALTMAN;AYOUB;AMARAL, 2011;DORNELLES;POCAHY, 2014;PINTO, 2011;TORRES;PRADO, 2014;ROCHA, 2012;XAVIER FILHA, 2012;SOARES, 2014;ALONSO;ZURBRIGGEN, 2014;EHRENBERG, 2014;DORNELLES, 2012;MOIZÉS;BUENO, 2010). In this perspective, the status of more than 60% of the produced literature on the subject suggests that the approach of the themes of body, gender and sexuality in teacher education contributes to the destabilization of norms, classifications and hierarchies surrounding the subject.…”
Section: The Development Of the Meta-analysismentioning
confidence: 97%
“…In Table 6 you can see the frequency of articles by type of effect. It can be observed that in the researched literature, the results are statis tically significant in 60.87% of production, totaling 14 articles (SEFFNER, 2011;WENETZ, 2012;RABELO, 2013;ALTMAN;AYOUB;AMARAL, 2011;DORNELLES;POCAHY, 2014;PINTO, 2011;TORRES;PRADO, 2014;ROCHA, 2012;XAVIER FILHA, 2012;SOARES, 2014;ALONSO;ZURBRIGGEN, 2014;EHRENBERG, 2014;DORNELLES, 2012;MOIZÉS;BUENO, 2010). In this perspective, the status of more than 60% of the produced literature on the subject suggests that the approach of the themes of body, gender and sexuality in teacher education contributes to the destabilization of norms, classifications and hierarchies surrounding the subject.…”
Section: The Development Of the Meta-analysismentioning
confidence: 97%
“…However, culture simultaneously implicates both a conscious and an unconscious level [for individuals] which determine their actions [22].…”
Section: A29mentioning
confidence: 99%
“…Adolescent girls are unable to negotiate condom use despite the fact that they cannot be sure about their partners' faithfulness [21]. They fear that asking for a condom cause a situation of embarrassment in the relationship and lead to the loss of their partners [22].…”
Section: A12mentioning
confidence: 99%
“…A pesquisa indicou que gênero, na perspectiva pós-estruturalista, é compreendido como uma construção discursiva, histórica e cultural e não mais uma categoria natural ou dada a partir do sexo biológico (Beiras, Tagliamento, & Toneli;2005;Bento, 2011;Dinis, 2008;César, 2009;Cruz, 2011;Félix & Palafox, 2009;Ferrari & Almeira, 2012;Furlani, 2007;Gesser e cols., 2012;Gomes, 2006;Lionço & Diniz, 2008;Maia, Navarro & Maia, 2011;Quirino & Rocha, 2012;Rosistolato, 2009;Rohden, 2009;Alós, 2011;Toneli, 2006;Wenetz, Stigger & Meyer, 2013;Wenetz, 2012). Portanto, com base nessa perspectiva, não são as características sexuais que marcam as diferenças entre homens e mulheres, mas o modo como elas são representadas e valorizadas na sociedade.…”
Section: Conceito De Gênero Na Produção Do Conhecimento Sobre Diversiunclassified